PENGARUH KOFEINA TERHADAP KELARUTAN DAN KETERSEDIAAN HAYATI O-ETOKSIBENZAMIDA PADA TIKUS JANTAN. - Yuwono, Tedjo
The effort to increase the bioavailability of o-ethoxybenzamide using a substance, which increases its solubility, has been investigated. To carry out this purpose, caffeine was used as the solubilizing agent. Three aspect of the effect of caffeine on o-ethoxybenzamide properties have been studied in this investigation, i.e. the solubility, the bioavailability, and the analgesic potency of o-ethoxybenzamide. Male laboratory rats were used for the bioavailability experiments, and the effect of caffeine on the analgesic potency of o-ethoxybenzamide was studied by modified Siegmund et al. method, using female laboratory mice. - Some preliminary studies, i.e. the effect of caffeine on the solubility, dissolution rate and chloroform-water partition coefficient of o-ethoxybenzamide were carried out. The effect of this substance on the intestinal permeability of the in vitro absorption of o-ethoxybenzamide was studied as well. The results of these studies showed that caffeine has a positive effect on the solubility of o-ethoxybenzamide, that the former increased the solubility and also the dissolution rate of o-ethoxybenzamide. However, caffeine rather decreased the chloroform-water partition coefficient of o-ethoxybenzamide. It has been proven, that caffeine did not change the intestinal permeability of the in vitro absorption of oethoxybenzamide. Considering to the result of the preliminary studies, these indicated that caffeine could increase the in vivo absorption ofo-ethoxybenzamide from the intestine, furthermore its bioavailability would be increased, which has been proven by in vivo experiments using male laboratory rats. The simultaneous oral administration of caffeine 16 mg/kg body weight and o-ethoxybenzamide 80 mg/kg body weight increased the bioavailability of o-ethoxybenzamide. The peak of the plasma level increased from 32,0 pg m1-1 to 38,6 pg m1 -1 , and the area under curve until 180 minutes (A3c 180 minutes) increased from 2847 pg minute m1-1 to 5852 pg minute m1 1 . Both were statistically significant difference (P = 0,01). Although there was an evidence that caffeine increased the absorption of o-ethoxybenzamide, it seems according to the analgesic experiments that caffeine tended to decrease the analgesic potency of o-ethoxybenzamide, and the decreasing of this potency was equal to the dose of caffeine. The conclusion of this investigation is, that the rate limiting step of o-ethoxybenzamide absorption process is the dissolution rate. So the bioavailability of o-ethoxybenzamide will increase by increasing its solubility or its dissolution rate. It was suggested to investigate the effect of caffeine on the metabolism rate and the pharmacokinetic pattern of o-ethoxybenzamide.